Method for improving mechanical property of additive manufacturing Ti2AlNb alloy

Through a specific heat treatment program, the grain boundary continuous α2 phases in the additive manufacturing Ti2AlNb alloy are eliminated, forming a single-phase β structure of fine grains, solving the problem of poor mechanical properties of the additive manufacturing Ti2AlNb alloy and significantly improving the tensile resistance of the material Strength, suitable for complex aerospace structures.

CN119121090AActive Publication Date: 2024-12-13AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411278489.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The comprehensive mechanical properties of the deposition structure formed by the additive manufacturing Ti2AlNb alloy during cooling are poor, resulting in the continuous formation of α2 phases of the grain boundary after heat treatment, which is prone to cracks, affecting the mechanical properties, and it is difficult to meet the needs of complex aerospace structures.

Method used

A specific heat treatment program, including multiple cycles of heating and cooling, gradually eliminates the continuous α2 phase of grain boundaries, and promotes the complete dissolution and precipitation of α2 phase and O phase by adjusting the temperature rise rate, insulation temperature and time, forming a single grain of fine grains. The phase β structure is used to avoid the formation of continuous α2 phases in the grain boundary.

Benefits of technology

It effectively eliminates the continuous precipitation phase of grain boundaries, improves the mechanical properties of the material, improves the tensile strength of the material, and meets the application needs of complex aerospace structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121090A_ABST
    Figure CN119121090A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal materials, and particularly relates to a method for improving the mechanical property of an additive manufacturing Ti2AlNb alloy, which comprises the following steps of: heating an additive manufacturing Ti2AlNb alloy part to 10-20 DEG C above a beta phase transformation point at the speed of 30 + / -10 DEG C / min, keeping the temperature for 2-8 hours, and cooling to the environment temperature; then, the part is heated to 20-50 DEG C below the beta phase transformation point at the speed of 10 + / -5 DEG C / min, heat preservation is conducted for 1-4 h, and the part is cooled to the environment temperature; then, the part is heated to 10-20 DEG C below the beta phase transformation point at the speed of 10 + / -5 DEG C / min, heat preservation is carried out for 0.5-2 h, the part is cooled to 10-20 DEG C above the alpha2 phase transformation point, the treatment is repeated for 1-3 times, and the part is cooled to the environment temperature; and finally, the part is heated to 50-150 DEG C below the alpha2 phase transformation point at the speed of 10 + / -5 DEG C / min, heat preservation is conducted for 22-26 h, and the part is cooled to the environment temperature. According to the method provided by the invention, the mechanical strength of the Ti2AlNb alloy manufactured by the additive can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and in particular relates to a method for improving the mechanical properties of an additively manufactured Ti2AlNb alloy. Background Art

[0002] Ti2AlNb alloy is an intermetallic compound with a density of 5.3g / cm 3 ~5.4g / cm 3 The long-term use temperature can reach 650℃~750℃. It has good mechanical properties such as room temperature plasticity, toughness, good high temperature strength, and has good processing performance, comprehensive mechanical properties, and good flame retardant properties. It is considered to be an important lightweight and high temperature resistant structural material that can replace nickel-based high temperature alloys in the aerospace field.

[0003] With the rapid advancement of aerospace technology, parts of aircraft, aero engines and spacecraft are also developing towards large-scale, complex and integrated directions. Traditional processing methods such as forging and casting have gradually become unable to meet the manufacturing needs of complex aerospace structural parts. Additive manufacturing technology completes part manufacturing by layer-by-layer deposition, which is a near-net-shape forming process without the use of molds. Compared with traditional manufacturing methods, it is more suitable for high-quality rapid manufacturing of complex structure Ti2AlNb alloy parts.

[0004] However, the additive manufacturing process cools quickly, and the comprehensive mechanical properties of the deposited microstructure of the additively manufactured Ti2AlNb alloy are poor, and heat treatment is required to improve its comprehensive mechanical properties. However, due to the component segregation at the grain boundary during the solidification of the additive manufacturing molten pool, a continuous α2 phase will be formed at the grain boundary after the additively manufactured Ti2AlNb alloy is heat treated using the current conventional solid solution aging method. During the use of the additively manufactured Ti2AlNb alloy, cracks are easily formed at the continuous α2 phase at the grain boundary, resulting in premature aging of the material, adversely affecting the mechanical properties, and causing the material to fail to meet application requirements. Therefore, it is necessary to invent a heat treatment system for the special forming process and microstructure of the additively manufactured Ti2AlNb alloy to improve the mechanical properties of the material. Summary of the invention

[0005] In view of this, an object of the present invention is to provide a method for improving the mechanical properties of additively manufactured Ti2AlNb alloy, which can improve the material strength of the additively manufactured Ti2AlNb alloy while maintaining good plasticity, thereby promoting the engineering application of the additively manufactured Ti2AlNb alloy.

[0006] The present invention provides a method for improving the mechanical properties of an additively manufactured Ti2AlNb alloy, comprising the following steps:

[0007] Step 1: Place the additively manufactured Ti2AlNb alloy parts into a heating furnace, heat them from ambient temperature to a temperature range of 10 to 20 °C above the β phase transformation point at a heating rate of 30 ± 10 °C / min, keep them warm for 2 to 8 hours, and then cool them to ambient temperature;

[0008] Step 2: Place the parts processed in step 1 into a heating furnace, heat them to a temperature range of 20 to 50°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 1 to 4 hours, and then cool them to ambient temperature;

[0009] Step 3: Place the parts processed in step 2 into a heating furnace, heat them to a temperature range of 10 to 20°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 0.5 to 2h, and then cool them to a temperature range of 10 to 20°C above the α2 phase transition point;

[0010] Step 4: Repeat step 3 1 to 3 times. During the last repetition, after the temperature is kept within a range of 10 to 20°C below the β phase transition point, cool to ambient temperature.

[0011] Step 5: Place the parts processed in step 4 into a heating furnace, heat them to a temperature range of 50 to 150 °C below the α2 phase transition point at a heating rate of 10 ± 5 °C / min, keep them warm for 22 to 26 hours, and then cool them to ambient temperature.

[0012] Preferably, the Al content of the Ti2AlNb alloy is 18-30at%.

[0013] Preferably, the Nb content of the Ti2AlNb alloy is 10 to 30 at%.

[0014] Preferably, the β phase transition point of the Ti2AlNb alloy is obtained by differential scanning calorimetry or metallographic method.

[0015] Preferably, the α2 phase transition point of the Ti2AlNb alloy is obtained by differential scanning calorimetry or metallographic method.

[0016] Preferably, the heating furnace used in step one is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

[0017] Preferably, the heating furnace used in step 2 is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

[0018] Preferably, the heating furnace used in step three and step four is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method in step four is air cooling.

[0019] Preferably, the heating furnace used in step five is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

[0020] Preferably, the ambient temperature is 5-40°C.

[0021] The traditional forged / cast Ti2AlNb alloy heat treatment system is a solution aging treatment. After the solution aging treatment, the additively manufactured Ti2AlNb alloy will form a continuous α2 phase at the grain boundary. During the use of the alloy, cracks are prone to initiate and expand at the continuous precipitation phase at the grain boundary, resulting in a decrease in the strength of the alloy. For the above problems, the scheme of the present invention has been targeted to solve them. The treatment in step one can completely dissolve the α2 phase and the O phase in the deposited structure of the additively manufactured Ti2AlNb alloy, promote atomic diffusion inside the material, eliminate the grain boundary segregation formed during the solidification process, inhibit the formation of continuous α2 phase at the grain boundary during the subsequent heat treatment, and will not cause the grains to grow. The fine grains formed during the rapid cooling process of the additive manufacturing are maintained, ensuring that the material has good mechanical properties, and finally forming a single-phase β structure with fine grains. A heating rate of less than 30±10℃ / min will cause the formation of precipitation phases during the heating process, and a heating rate of more than 30±10℃ / min will cause excessive stress and cracking. Therefore, the heating rate is selected at 30±10℃ / min. When the holding temperature is less than 10-20℃ above the β phase transformation point, the α2 phase and O phase formed in the deposited structure cannot be completely dissolved, the grain boundary segregation formed during the solidification process cannot be eliminated, and the formation of continuous α2 phase at the grain boundary during the subsequent heat treatment process cannot be inhibited. When the holding temperature is greater than 10-20℃ above the β phase transformation point, the grains will grow and the mechanical properties of the material will be destroyed. Therefore, the holding temperature is selected in the temperature range of 10-20℃ above the β phase transformation point. When the holding time is less than 2h, the atomic diffusion is insufficient and the effect of eliminating grain boundary segregation cannot be achieved. When the holding time is greater than 8h, there is no significant improvement in the effect of eliminating grain boundary segregation, but it reduces the production efficiency. Therefore, the holding time is selected in the range of 2-8h. After the treatment in step 2, the α2 phase will precipitate from the β phase matrix, and the microstructure of the material is composed of the β phase matrix and the α2 phase. Although this organizational morphology improves the mechanical properties of the material to a certain extent, it will also form a continuous α2 phase at the grain boundary. When the heating rate is less than 10±5℃ / min, the heating process is too long, which reduces the production efficiency. When the heating rate is greater than 10±5℃ / min, it is difficult for the α2 phase to be fully precipitated, and the effect of improving the mechanical properties is not achieved. Therefore, the heating rate is selected to be 10±5℃ / min. The purpose of keeping warm in the temperature range of 20-50℃ below the β phase transformation point is to maintain the material with good comprehensive mechanical properties. If the holding temperature is too high, the α2 phase content is too small, and if the holding temperature is too low, the β phase matrix content is too small. If the holding time is less than 1h, the α2 phase is difficult to be fully precipitated, and the effect of improving the mechanical properties is not achieved. A holding time greater than 4h has no obvious effect on the precipitation of the α2 phase, but reduces the production efficiency. Therefore, the holding time is selected to be 1-4h. The purpose of steps three to four is to heat the material to the upper part of the β+α2 phase region and then cool it to the lower part of the β+α2 phase region. In a heating and cooling process, the continuous α2 phase at the grain boundary will be spheroidized, but not completely disconnected.By performing multiple cycles of heating / cooling treatment, the decomposition of the continuous α2 phase at the grain boundary can be further promoted, the degree of disconnection of the continuous α2 phase at the grain boundary can be increased, and the purpose of eliminating the continuous α2 phase at the grain boundary can be achieved. Compared with continuous heat preservation treatment, the use of multiple cycles of heating / cooling treatment can intermittently increase the concentration difference of solute elements, and the discontinuity effect of the continuous α2 phase at the grain boundary is better. The best effect of destroying the continuous α2 phase at the grain boundary can be achieved in the temperature range of 10-20°C below the β phase transformation point to 10-20°C above the α2 phase transformation point. If the holding temperature is too high, the α2 phase content is too small, and if the holding temperature is too low, the β phase matrix content is too small. When the holding time is less than 0.5h, the α2 phase is difficult to be fully disconnected, and the effect of improving the mechanical properties cannot be achieved. When the holding time is greater than 2h, there is no obvious effect on the disconnection of the α2 phase, but it reduces the production efficiency. Therefore, the holding time is selected to be 0.5-2h. When the heating rate is less than 10±5℃ / min, the heating process is too long, which reduces the production efficiency. When the heating rate is greater than 10±5℃ / min, the α2 phase is difficult to fully disconnect. Therefore, the heating rate is selected at 10±5℃ / min. The effect of repeating step three 1 to 3 times is that the number of cycles is too small to achieve the purpose of discontinuous grain boundary α2 phase. As the number of cycles increases, the aspect ratio of the α2 phase will decrease, the concentration difference between the top and both sides of the α2 phase will become smaller and smaller, and diffusion will become more and more difficult. As a result, further increasing the number of cycles will not significantly change the degree of discontinuity of the continuous α2 phase at the grain boundary, but will extend the production time and reduce efficiency. Therefore, the number of repetitions of step three is set to 1 to 3 times. The purpose of step five is to promote the precipitation of O phase and secondary α2 phase and further improve the mechanical properties of the material. If the holding temperature is too high, the O phase content is too low. If the holding temperature is too high, the β phase content is too low, which is not conducive to the mechanical properties of the material. Therefore, the holding temperature is selected in the temperature range of 50 to 150℃ below the α2 phase transformation point. When the holding time is less than 22h, it is difficult for the O phase and the secondary α2 phase to be fully precipitated, and the content is low, which does not improve the mechanical properties. When the holding time is greater than 26h, there is no obvious effect on the formation of the precipitated phase, but it reduces the production efficiency. Therefore, the holding time is selected to be 22-26h. When the heating rate is less than 10±5℃ / min, the heating process is too long, which reduces the production efficiency. When the heating rate is greater than 10±5℃ / min, it is difficult for the O phase and the secondary α2 phase to be fully precipitated. Therefore, the heating rate is selected to be 10±5℃ / min.

[0022] The experimental results show that the additively manufactured Ti2AlNb alloy treated by the method of the present invention eliminates the continuous precipitation phase at the grain boundary and improves the mechanical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0024] Figure 1 A heat treatment process flow chart of the additive manufacturing Ti2AlNb alloy provided in an embodiment of the present invention;

[0025] Figure 2 A microstructure photograph of the additively manufactured Ti2AlNb alloy part after treatment provided in Comparative Example 1 of the present invention;

[0026] Figure 3 This is a microstructure photograph of the additively manufactured Ti2AlNb alloy part after treatment provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention provides a method for improving the mechanical properties of Ti2AlNb alloys manufactured by additive manufacturing, referring to Figure 1 , including the following steps:

[0029] Step 1: Place the additively manufactured Ti2AlNb alloy parts into a heating furnace, heat them from ambient temperature to a temperature range of 10 to 20 °C above the β phase transformation point at a heating rate of 30 ± 10 °C / min, keep them warm for 2 to 8 hours, and then cool them to ambient temperature;

[0030] Step 2: Place the parts processed in step 1 into a heating furnace, heat them to a temperature range of 20 to 50°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 1 to 4 hours, and then cool them to ambient temperature;

[0031] Step 3: Place the parts processed in step 2 into a heating furnace, heat them to a temperature range of 10 to 20°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 0.5 to 2h, and then cool them to a temperature range of 10 to 20°C above the α2 phase transition point;

[0032] Step 4: Repeat step 3 1 to 3 times. During the last repetition, after the temperature is kept within a range of 10 to 20°C below the β phase transition point, cool to ambient temperature.

[0033] Step 5: Place the parts processed in step 4 into a heating furnace, heat them to a temperature range of 50 to 150 °C below the α2 phase transition point at a heating rate of 10 ± 5 °C / min, keep them warm for 22 to 26 hours, and then cool them to ambient temperature.

[0034] In the method provided by the present invention, the Al content of the Ti2AlNb alloy is preferably 18-30at%, specifically 18at%, 19at%, 20at%, 21at%, 22at%, 23at%, 24at%, 25at%, 26at%, 27at%, 28at%, 29at% or 30at%; the Nb content of the Ti2AlNb alloy is preferably 10-30at%, specifically 10at%, 11at%, 12at%, 13at%, 14at%, 15at%, 16at%, 17at%, 18at%, 19at%, 20at%, 21at%, 22at%, 23at%, 24at%, 25at%, 26at%, 27at%, 28at%, 29at% or 30at%.

[0035] In the method provided by the present invention, the β phase transition point and the α2 phase transition point of the Ti2AlNb alloy are preferably obtained by differential scanning calorimetry or metallographic method.

[0036] In the method provided by the present invention, the ambient temperature is preferably 5-40°C, specifically 5°C, 10°C, 15°C, 20°C, 25°C (room temperature), 30°C, 35°C or 40°C.

[0037] In the method provided by the present invention, in step 1, the heating furnace used is preferably a vacuum heating furnace or an atmosphere protection furnace.

[0038] In the method provided by the present invention, in step one, the heating rate can be specifically 20℃ / min, 21℃ / min, 22℃ / min, 23℃ / min, 24℃ / min, 25℃ / min, 26℃ / min, 27℃ / min, 28℃ / min, 29℃ / min, 30℃ / min, 31℃ / min, 32℃ / min, 33℃ / min, 34℃ / min, 35℃ / min, 36℃ / min, 37℃ / min, 38℃ / min, 39℃ / min or 40℃ / min.

[0039] In the method provided by the present invention, in step one, the temperature can be heated in the furnace to 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C above the β phase transition point.

[0040] In the method provided by the present invention, in step 1, the insulation time can be specifically 2h, 3h, 4h, 5h, 6h, 7h or 8h.

[0041] In the method provided by the present invention, in step 1, the cooling method is preferably air cooling.

[0042] In the method provided by the present invention, in step 2, the heating furnace used is preferably a vacuum heating furnace or an atmosphere protection furnace.

[0043] In the method provided by the present invention, in step 2, the heating rate can be specifically 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min.

[0044] In the method provided by the present invention, in step 2, the temperature can be heated in the furnace to 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C below the β transition point.

[0045] In the method provided by the present invention, in step 2, the insulation time can be specifically 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0046] In the method provided by the present invention, in step 2, the cooling method is preferably air cooling.

[0047] In the method provided by the present invention, in step three, the heating furnace used is preferably a vacuum heating furnace or an atmosphere protection furnace.

[0048] In the method provided by the present invention, in step three, the heating rate can be specifically 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min.

[0049] In the method provided by the present invention, in step three, the temperature can be heated in the furnace to 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C below the β phase transition point.

[0050] In the method provided by the present invention, in step three, the insulation time can be specifically 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h.

[0051] In the method provided by the present invention, in step three, the furnace cooling can be specifically to 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C above the α2 phase transition point.

[0052] In the method provided by the present invention, in step 4, step 3 may be repeated 1 time, 2 times or 3 times.

[0053] In the method provided by the present invention, in step 4, the heating furnace used is preferably a vacuum heating furnace or an atmosphere protection furnace.

[0054] In the method provided by the present invention, in step 4, the cooling method is preferably air cooling.

[0055] In the method provided by the present invention, in step five, the heating furnace used is preferably a vacuum heating furnace or an atmosphere protection furnace.

[0056] In the method provided by the present invention, in step five, the heating rate can be specifically 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min.

[0057] In the method provided by the present invention, in step five, the furnace can be heated to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C below the α2 phase transition point.

[0058] In the method provided by the present invention, in step five, the insulation time can be specifically 22h, 22.5h, 23h, 23.5h, 24h, 24.5h, 25h, 25.5h or 26h.

[0059] In the method provided by the present invention, in step 5, the cooling method is preferably air cooling.

[0060] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0061] Comparative Example 1

[0062] This comparative example provides the treatment steps of the additively manufactured Ti2AlNb alloy with a chemical composition of Ti-22Al-10Nb (at%) using a solid solution aging heat treatment method:

[0063] Step 1: Place the additively manufactured Ti2AlNb alloy part into a heating furnace, heat it from room temperature to 980°C at a heating rate of 30°C / min, keep it warm for 1h, and then air cool it to room temperature;

[0064] Step 2: The parts processed in step 1 are placed in a heating furnace, heated to 790° C. at a heating rate of 30° C. / min, kept at that temperature for 24 hours, and then air-cooled to room temperature.

[0065] The microstructure of the additively manufactured Ti2AlNb alloy parts after treatment in this comparative example was observed, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that there is a continuous α2 phase at the grain boundary.

[0066] Example 1

[0067] This embodiment provides a method for improving the mechanical properties of an additively manufactured Ti2AlNb alloy having a chemical composition of Ti-22Al-10Nb (at%), wherein the β phase transition point of the alloy is 1100° C. and the α2 phase transition point is 980° C., and comprises the following steps:

[0068] Step 1: Place the additively manufactured Ti2AlNb alloy parts into a heating furnace, heat them from room temperature to 1120°C at a heating rate of 30°C / min, keep them warm for 5 hours, and then air cool them to room temperature;

[0069] Step 2: The parts processed in step 1 are placed in a heating furnace, heated to 1060°C at a heating rate of 10°C / min, kept at this temperature for 3 hours, and then air-cooled to room temperature;

[0070] Step 3: Place the parts processed in step 2 into a heating furnace, heat them to 1080°C at a heating rate of 10°C / min, keep them warm for 1 hour, and then cool them to 1000°C. Then, heat them to 1080°C at a heating rate of 10°C / min, keep them warm for 1 hour, and then cool them to 1000°C. Then, heat them to 1080°C at a heating rate of 10°C / min, keep them warm for 1 hour, and then air cool them to room temperature.

[0071] Step 4: Place the parts processed in step 3 into a heating furnace, heat to 920° C. at a heating rate of 10° C. / min, keep warm for 24 hours, and then air-cool to room temperature.

[0072] The microstructure of the additively manufactured Ti2AlNb alloy parts treated in this embodiment was observed, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that there is a discontinuous α2 phase at the grain boundary.

[0073] Example 2

[0074] This embodiment provides a method for improving the mechanical properties of an additively manufactured Ti2AlNb alloy having a chemical composition of Ti-22Al-25Nb (at%), wherein the β phase transition point of the alloy is 1080°C and the α2 phase transition point is 1010°C, and comprises the following steps:

[0075] Step 1: Place the additively manufactured Ti2AlNb alloy part into a heating furnace, heat it from room temperature to 1090°C at a heating rate of 40°C / min, keep it warm for 8 hours, and then air cool it to room temperature;

[0076] Step 2: The parts processed in step 1 are placed in a heating furnace, heated to 1040°C at a heating rate of 5°C / min, kept at that temperature for 1 hour, and then air-cooled to room temperature;

[0077] Step 3: Place the parts processed in step 2 into a heating furnace, heat them to 1060°C at a heating rate of 5°C / min, keep them warm for 2 hours, and then cool them to 1030°C. Then, heat them to 1060°C at a heating rate of 5°C / min, keep them warm for 2 hours, and then cool them to 1030°C. Then, heat them to 1060°C at a heating rate of 5°C / min, keep them warm for 2 hours, and then cool them to 1030°C. Then, heat them to 1060°C at a heating rate of 5°C / min, keep them warm for 2 hours, and then air cool them to room temperature.

[0078] Step 4: Place the parts processed in step 3 into a heating furnace, heat to 910° C. at a heating rate of 5° C. / min, keep warm for 22 hours, and then air-cool to room temperature.

[0079] The tensile strength of the additively manufactured Ti2AlNb alloys treated by Comparative Example 1 and Examples 1-2 was tested. The results showed that the room temperature tensile strength of the additively manufactured Ti2AlNb alloys treated by Example 1 and Example 2 reached 1134 MPa and 1126 MPa, respectively, while the room temperature tensile strength of the additively manufactured Ti2AlNb alloy in Comparative Example 1 using the traditional solution aging heat treatment method was only 962 MPa. The treatment effect of the examples was significantly improved compared with the comparative examples.

[0080] Special note: The technical solution of the present invention involves different alloy components and many process parameters. It is necessary to comprehensively consider the synergistic effect between the alloy components and the process parameters in order to obtain the beneficial effects and significant progress of the present invention.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the mechanical properties of Ti2AlNb alloy produced by additive manufacturing, characterized in that: The following steps are involved: Step 1: Place the additively manufactured Ti2AlNb alloy parts into a heating furnace, heat them from ambient temperature to a temperature range of 10 to 20 °C above the β phase transformation point at a heating rate of 30 ± 10 °C / min, keep them warm for 2 to 8 hours, and then cool them to ambient temperature; Step 2: Place the parts processed in step 1 into a heating furnace, heat them to a temperature range of 20 to 50°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 1 to 4 hours, and then cool them to ambient temperature; Step 3: Place the parts processed in step 2 into a heating furnace, heat them to a temperature range of 10 to 20°C below the β phase transition point at a heating rate of 10±5°C / min, keep them warm for 0.5 to 2h, and then cool them to a temperature range of 10 to 20°C above the α2 phase transition point; Step 4: Repeat step 3 1 to 3 times. During the last repetition, after the temperature is kept within a range of 10 to 20°C below the β phase transition point, cool to ambient temperature. Step 5: Place the parts processed in step 4 into a heating furnace, heat them to a temperature range of 50 to 150°C below the α2 phase transition point at a heating rate of 10±5°C / min, keep them warm for 22 to 26 hours, and then cool them to ambient temperature.

2. The method according to claim 1, characterized in that The Al content of the Ti2AlNb alloy is 18-30 at %.

3. The method according to claim 1, characterized in that The Nb content of the Ti2AlNb alloy is 10-30 at %.

4. The method according to claim 1, characterized in that The β phase transition point of the Ti2AlNb alloy is obtained by differential scanning calorimetry or metallographic method.

5. The method according to claim 1, characterized in that The α2 phase transition point of the Ti2AlNb alloy is obtained by differential scanning calorimetry or metallographic method.

6. The method according to claim 1, characterized in that The heating furnace used in step 1 is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

7. The method according to claim 1, characterized in that The heating furnace used in step 2 is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

8. The method according to claim 1, characterized in that The heating furnace used in step 3 and step 4 is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method in step 4 is air cooling.

9. The method according to claim 1, characterized in that: The heating furnace used in step 5 is a vacuum heating furnace or an atmosphere protection furnace, and the cooling method is air cooling.

10. The method according to any one of claims 1 to 9, characterized in that: The ambient temperature is 5-40°C.

Citation Information

Patent Citations

  • Method for obtaining B2+O / alpha2 multi-morphology stable structures through pre-deformation of Ti-22Al-25Nb alloy

    CN108660399A

  • Heat treatment process of three-phase Ti2AlNb-based alloy manufactured by laser additives

    CN109332693A

  • Heat treatment process for improving obdurability of near beta type or metastable beta type titanium alloy

    CN110923598A

  • Heat treatment method for arc additive manufacturing high-strength titanium alloy and enhanced high-strength titanium alloy

    CN111826594A

  • Heat treatment technology for improving endurance and creep properties of Ti2AlNb-based alloy

    CN112063945A